Rhabdomyosarcoma of the Head and Neck: A Multimodal Approach - Casey, Dana L.; Wolden, Suzanne L. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Head and neck rhabdomyosarcoma (HNRMS) is a uniquely challenging site to treat given the young patient age and critical anatomy of the head and neck region. We review the characteristics, management, and future directions in the treatment of HNRMS. Most patients who present with HNRMS have unresectable disease due to functional and/or cosmetic constraints. However, surgical resection and brachytherapy serve a critical role in select patients. The treatment paradigm for the majority of patients with HNRMS consists of definitive chemotherapy and radiation therapy. As the incidence of late toxicities increases with improved survival, modern efforts must focus on ways to decrease long-term morbidity. We recommend a multimodal approach emphasizing the preservation of form and function for the treatment of HNRMS.
Keywords: pediatric rhabdomyosarcoma; head and neck neoplasms; radiotherapy; brachytherapy